Determinants of general health perception among individuals with chronic low back pain overtime: structural equation modeling. - Owis Eilayyan; Line Enjalbert-Auneau; Sara Ahmed (PLoS ONE)
Background Low back pain (LBP) is a public health problem. General health perception is the best predictor of healthcare utilization and mortality. Identifying predictors of health perception helps understand how people with LBP live, implement the appropriate treatment, and improve the quality of care. Objective This study aimed to estimate the relationships between pain intensity, psychological distress, self-efficacy, functional ability, and healthcare utilization among individuals with chronic LBP over a period of six-months and to estimate the impact of these relationships on general health perception. Methods This is a secondary analysis of data from a longitudinal study that assessed the health outcomes of individuals with chronic LBP. Structural equation modeling (SEM), based on health frameworks, was used to estimate the predictors of health perception among people with LBP at baseline and 6-months. Results 314 individuals with LBP were included in the analysis. The final SEM model had good fit statistics and explained 48% of health perception variance at 6-months. The model showed that health perception was significantly affected by pain intensity (β = 0.29, β = 0.21), psychological distress (β = 0.51, β = 0.44) and self-efficacy (β = 0.4, β = 0.36) cross-sectionally and overtime, respectively. Conclusion Different health outcomes could affect the health perception among people with low back pain. This requires holistic approaches to treatment, involving self-management and cognitive behavioral therapy, as well as improved self-efficacy to improve their health.